Examining the Roles of Self-Efficacy, Attitude and Self-Regulated Learning through Augmented Reality in Reading for EFL Learners - Yulian, Ryani; Yuniarti, Yuniarti; Sirat, Okta Miftahul (Universitas Pendidikan Ganesha, 2023)
In recent years, higher education institutions have faced challenges in the field of education. The impact of digital technology such as augmented reality increases the possibility of self -regulated learning. Therefore this study analyze the relationship between self-efficacy, attitude and self-regulated learning across cognition, motivation, behaviour, and context through augmented reality in reading for English as foreign language (EFL) learners. Data were collected from 213 undergraduate students in English for Specific Class (ESP) in an academic university in Indonesia. This study was used a non-experimental, analytic survey research design with SmartPLS. The study assessed the measurement model of the factor loadings, composite reliability, and convergent validity, and employed bootstrapping for p-values of the path coefficient. The findings of the study reported that self-efficacy has a statistically significant relationship with cognition, motivation, behaviour and context while attitude has a statistically positive relationship with motivation and context but not with cognition and behavior.